a+b=6,ab=-8.①a平方+b平方=②a平方-ab+b平方=③(a-b)的平方=
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 03:12:41
a+b=6,ab=-8.①a平方+b平方=②a平方-ab+b平方=③(a-b)的平方=a+b=6,ab=-8.①a平方+b平方=②a平方-ab+b平方=③(a-b)的平方=a+b=6,ab=-8.①a
a+b=6,ab=-8.①a平方+b平方=②a平方-ab+b平方=③(a-b)的平方=
a+b=6,ab=-8.
①a平方+b平方=
②a平方-ab+b平方=
③(a-b)的平方=
a+b=6,ab=-8.①a平方+b平方=②a平方-ab+b平方=③(a-b)的平方=
①a平方+b平方= (a+b)^2-2ab
②a平方-ab+b平方= (a+b)^2-3ab
③(a-b)的平方= (a+b)^2-4ab
哎.建议你看下书 这么简单
a^2+b^2=(a+b)^2-2ab=36+16=52
a平方-ab+b平方=(a+b)^2-3ab=36+24=60
(a-b)的平方=(a+b)^2-4ab=36+32=68
1)(a+b)^2=a^2+b^2+2ab=6*6=36,所以a^2+b^2=52
2)同理,a平方-ab+b平方= (a+b)^2-3ab=60
3)(a-b)的平方=52+16=68
a+b=6,ab=-8.①a平方+b平方=②a平方-ab+b平方=③(a-b)的平方=
已知ab=6 a平方b-ab平方-a+b=45 a平方+b平方的值
已知a平方+b平方=6ab,且a
a平方b平方+a平方+b平方+10ab+16=0 求a+b
a平方+b平方+a平方b平方+1=4ab求a .b各值
已知a平方-ab=6,ab-b平方=2,求a平方-2ab+b平方,a平方-b平方的值.
已知a平方-ab=6,ab-b平方=2,求a平方-2ab+b平方,a平方-b平方的值.就现在,越快越好
a的平方b-(-3ab平方)+(-4a平方b)-2ab平方=
a平方+b平方+1+ab^2=4ab、求a平方+b平方
a>b>0 a的平方+b的平方-6ab则(a-b分之a+b)的平方a>b>0 a的平方+b的平方-6ab=0则(a-b分之a+b)的平方
-2abx( )=4a平方b-6ab平方
已知a平方+ab=6,b平方+ab=4,求a平方-b平方和a平方+2ab+b平方
已知a的平方+ab=15,b的平方+ab=6 求a的平方+b的平方
已知ab=7,a+b=6求 a平方×b+a×b平方
若a+b=2,a平方+平方=6,则ab=_,(a-b)平方= ,ab平方+a平方b=
a+b=7,ab=12求a平方+b平方,求(a-b)平方
如果a平方+ab=15,b平方+ab=6,求a平方-b平方和a平方+b平方的值
如果a平方+ab=15,b平方+ab=6,求a平方-b平方和a平方+b平方的值